Effect of lemon essential oil on the microbial control, physicochemical properties, and aroma profiles of peeled shrimp. (1st January 2023) - Hung, Yueh-Hao Ronny; Lin, Hsuan-Ju; Lee, En-Chi; Lu, Wen-Jung; Lin, Yu-Ting; Huang, Bo-Bin; Lin, Tze-Chia; Lin, Hong-Ting Victor
Abstract: To extend the shelf-life of peeled shrimp, the risk of microbial contamination should be minimized. The aim of this study was to determine how the antimicrobial activity of citrus-based essential oils (EOs) benefits the shelf-life of peeled shrimp. Eight essential oils were screened for their inhibitory effects on shrimp spoilage bacteria in solid and vapor phase diffusion assays. The results indicated that folded lemon EO and grapefruit EO had relatively extensive and strong inhibitory effects on cell growth compared with the other EOs. Lemon EO was selected as a treatment for peeled shrimp in accelerated shelf-life testing at 30 °C. The final log CFU/g of total aerobic bacteria and lactic acid bacteria of the EO-treated groups was reduced by 20.7% and 21.6%, respectively, as compared with the control group. The TVB-N value in the EO-treated group was 9.03 mg/100 g at 72 h, whereas the one in the control group increased to 32.95 mg/100 g. The analysis of the physical characteristics and volatile compounds revealed that lemon oil retarded the deterioration of peeled shrimp during storage. Overall, this study supports the potential use of citrus EOs for the microbial control of peeled shrimp to help extend shelf-life. Highlights: The citrus essential oils exhibited antibacterial activity in solid and vapor phase. The chemical compositions of the essential oils were determined by using GC-MS. Limonene is the major volatile compound in lemon oil and grapefruit essential oil. The aroma profiles of the essential oils-treated peeled shrimp was determined. Lemon oil retarded the quality deterioration of the peeled shrimp during storage.